2022
DOI: 10.1155/2022/9118201
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Multidimensional Gray Theory on Higher Education Cooperation Projects under the Mobile Communication System

Abstract: Gray system theory is a new field of control theory, which is the product of applying cybernetics and methods to social and economic systems, and is also the product of the combination of control theory and operations research. It takes the gray system as the research object. Whitening, desalination, quantification, modeling, and optimization are the core of the gray system, and it aims to predict and control the development of various gray systems. The purpose of this paper is to study how to analyze and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Security and Communication Networks has retracted the article titled "Te Infuence of Multidimensional Gray Teory on Higher Education Cooperation Projects under the Mobile Communication System" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Te Infuence of Multidimensional Gray Teory on Higher Education Cooperation Projects under the Mobile Communication System" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%